Aquatic macrophytes potential for the simultaneous removal of heavy metals (Buenos Aires, Argentina) - Miretzky, Patricia (2004)
Heavy metal removal from water has been approached by using different technologies. Phytotechnologies, with an increasing development during the last two decades, involve using plants for metal removal. Three autochthonous floating macrophytes, common in pampean shallow lakes (Argentina), Pista stratiotes, Spirodela intermedia and Lemna minor were used in laboratory experiences for the simultaneously removal of several heavy metals (Fe, Cu, Zn, Mn, Cr and Pb) resulting from anthropogenic activity, in order to simulate a naturally polluted environment. The experiences were performed for different concentrations of metals along 15 days. High metal removal percentages were obtained for the 3 species and metals. L. minor did not survive the conditions of the experiment. High correlation between the final water and the macrophytes metal concentration was obtained, deviations were due to PbCrO 4 precipitation. The rate of metal uptake was dependent on the metal concentration for the 3 species studied.